NF‐E2–Related Factor 2 Regulates Interferon Receptor Expression and Alters Macrophage Polarization in Lupus. Issue 10 (9th August 2020) - Han, Shuhong; Zhuang, Haoyang; Lee, Pui Y.; Li, Mingjia; Yang, Lijun; Nigrovic, Peter A.; Reeves, Westley H.
Abstract : Objective: Pristane‐induced lupus is associated with nonresolving inflammation and deficiency of proresolving macrophages. Proresolving nonclassic macrophages (NCMs) are less responsive to type I interferon (IFN) than classic macrophages (CMs; which are proinflammatory), reflecting their relative expression levels of the type I IFN receptor (IFNAR). This study was undertaken to investigate the regulation of IFNAR expression in macrophages. Methods: We carried out gene expression profiling of purified CMs and NCMs from mice treated with pristane (which develop lupus) or mineral oil (non‐lupus controls). Macrophage differentiation and IFNAR expression were examined in mice treated with NF‐E2–related factor 2 (Nrf2) activators and inhibitors and in Nrf2‐deficient mice. Nrf2 activity was also assessed in blood cells from patients with systemic lupus erythematosus (SLE). Significant differences were determined by Student's t ‐test. Results: RNA sequencing revealed increased expression of genes regulated by the transcription factor Nrf2 in NCMs from mineral oil–treated versus pristane‐treated mice and in NCMs versus CMs. The Nrf2 activator CDDO‐imidazole (CDDO‐Im) decreased CMs ( P < 0.0001) and promoted the development of proresolving NCMs ( P = 0.06), whereas the Nrf2 inhibitor brusatol increased CMs ( P < 0.05) and decreased NCMs ( P < 0.001). CDDO‐Im decreased Ifnar1 ( P < 0.001) and IFN‐stimulated gene (ISG) expression in macrophages and alleviated oxidative stress ( P < 0.05), whereas brusatol had the opposite effect ( P < 0.01). Moreover, Ifnar1 and ISG expression levels were higher in Nrf2‐knockout mice than controls ( P < 0.05). As seen in mice with lupus, SLE patients showed evidence of low Nrf2 activity. Conclusion: Our findings indicate that Nrf2 activation favors the resolution of chronic inflammation in lupus. Since autoantibody production and lupus nephritis depend on IFNAR signaling, the ability of Nrf2 activators to repolarize macrophages and reduce the INF signature suggests that these agents may warrant consideration for treating lupus.